Penguatan Literasi Siswa Sekolah Dasar Melalui Inisiasi Pojok Baca Di SD Negeri 5 Bedali Kediri Jawa Timur - Khairan; Muslikhatul Nur Rosyidah; Dwi Nanda A. Sidik; Fachniya Rahyoningtyas; Muhammad Ainul Hikam; Vera Vania (Pusmedia Group Indonesia, 2025)
The low level of literacy among elementary school students remains a serious issue in Indonesia. One of the main causes is the lack of access to a variety of reading materials and the limited availability of supporting facilities, such as adequate libraries. At SD Negeri 5 Bedali Kediri East Java, there is no library available, and most of the existing book collection consists of textbooks and old reading materials that are less appealing to students. This condition has led to low reading interest and suboptimal literacy skills among students. Therefore, this activity aims to improve students’ reading interest and literacy skills through the Reading Corner program as an alternative solution that facilitates direct access to reading materials within the classroom. The program was initiated by students from the 2025 Community Service Program (KKN) of the Islamic University of Tribakti Lirboyo Kediri (UIT), Group 18, as part of their community service in the field of education. The method used was descriptive qualitative research with an Asset-Based Community Development (ABCD) approach. Data were collected through observations and interviews with teachers, students, and the school environment. The implementation of the program included the planning stage, the creation of the reading corner, daily reading activities, and the evaluation and renewal of the reading corner’s content. The results of the activity showed a significant increase in students’ reading interest, positive behavioral changes, and greater enthusiasm in utilizing their free time for reading. Teachers and students gave positive responses to the existence of the reading corner, which has become an effective medium for strengthening literacy culture. The Reading Corner program proved effective in improving literacy in elementary schools, not only by expanding access to reading materials but also by helping to build a sustainable reading culture within the school environment. Thus, this initiative serves as an important solution in addressing the challenge of low literacy levels and supports the comprehensive development of students’ potential. Keywords : Strengthening Students’ Literacy; Reading Interest; Elementary Schools.